(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
In this note 8 species are reported for the first time from Islas del Rosario. They were found associated with Thalassia testudinum seagrass and Rhizophora mangle roots. With these new records, 242 species of fishes are now known in this area.